Studying the relationship between relationship marketing and improving marketing performance within the internal transport institutions in Syria (Field study in road transport companies) - لولو هبه; السكري أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to study the relationship of marketing with the marketing performance of customers of land transport companies, and the researcher relied on the descriptive analytical method as a general method of research. The research sample consisted of 150 individuals from the research community, which was represented by customers of land transport companies. The primary data was collected through the questionnaire as a study tool. The SPSS20 program was relied on as a tool for data analysis. And then the researcher conducted a field study, the results concluded that there is a direct relationship between relationship marketing and marketing performance, and that the dimensions most closely related to the criteria for evaluating marketing performance are customer complaints, followed by quality, where it was found that there is a direct and very strong relationship between customer complaints and customer satisfaction, and the relationship The somewhat acceptable difference between quality, complaints and loyalty is explained by the current economic situation What Syria suffers from, which is reflected on most customers by the deterioration of their financial conditions, as the customer today is turning to the company that asks for a lower price regardless of its application of quality and handling complaints, which are among the most important dimensions of relationship marketing.